Peran Kreativitas Guru Kristen Dan Motivasi Belajar Terhadap Prestasi Nara Didik - Boki, Patris; Pahabol, Natan; Marampa, Elieser R (Sekolah Tinggi Agama Kristen Diaspora, 2024)
This article examines the role of Christian teachers‘ creativity and learning motivation on students’ achievement. The purpose of this study is to analyse the extent to which teachers‘ creativity in teaching and students’ learning motivation affect their academic outcomes. The research method used is a descriptive qualitative approach with a literature study approach. It can be concluded that teacher creativity in delivering subject matter has a significant impact on student learning motivation. In addition, learning motivation is proven to be a key factor in improving students' academic achievement. The findings emphasise the importance of developing creative and effective teaching strategies to enhance learning motivation and, in turn, students' academic achievement in the context of Christian education. The role of the teacher also greatly influences students' learning motivation, hence the teacher should be able to adjust himself/herself with students so that they get a comfortable and pleasant learning atmosphere.AbstrakArtikel ini mengkaji peran kreativitas guru Kristen dan motivasi belajar terhadap prestasi peserta didik. Tujuan penelitian ini adalah untuk menganalisis sejauh mana kreativitas guru dalam mengajar dan motivasi belajar siswa memengaruhi hasil akademik mereka. Metode penelitian yang digunakan adalah pendekatan kualitatif deskritif dengan pendekekatan studi literature maka dapat disimpulkan bahwa kreativitas guru dalam menyampaikan materi pelajaran memiliki dampak signifikan terhadap motivasi belajar siswa. Selain itu, motivasi belajar terbukti menjadi faktor kunci dalam peningkatan prestasi akademik peserta didik. Temuan ini menekankan pentingnya mengembangkan strategi pengajaran yang kreatif dan efektif untuk meningkatkan motivasi belajar dan, pada gilirannya, prestasi akademik siswa dalam konteks pendidikan Kristen dan. Peran guru juga sangat mempengaruhi motivasi belajar siswa, maka dari itu guru harus bisa menyesuaikan dirinya dengan siswa agar mereka mendapatkan kenyamanan dan suasana belajar yang menyenangkan.